Цифровизация деятельности Пенсионного Фонда Украины - Кохан, В. П. (Право, 2020)
В статье рассмотрены проблемы цифровизации деятельности Пенсионного фонда Украины на примере реализации цифровых инфраструктур государственных (электронных) услуг и электронной идентификации граждан. Рассмотрены электронные услуги, предоставляемые Пенсионном фондом Украины, и средства электронной идентификации личности, необходимые для их получения. Сформулированы предложения по улучшению функционирования электронных сервисов Пенсионного фонда Украины. // The article discusses the problems of digitalization of the activities of the Pension Fund of Ukraine on the example of the implementation of digital infrastructures of state (electronic) services and electronic identification of citizens. Electronic services provided by the Pension Fund of Ukraine and the funds of the electronic identification of the person necessary for their receipt are considered. Deals on improving the functioning of electronic services of the Pension Fund of Ukraine are formulated.
Keywords: Пенсионный фонд Украины; электронные услуги; электронная идентификация личности; Pension Fund of Ukraine; electronic services; electronic identification of the personality